Microscopic Observation of Proliferative Membranes in Fibrocontractive Retinal Disorders. (28th July 2019) - Frisina, Rino; Tessarolo, Francesco; Marchesoni, Ivan; Piccoli, Federico; Bonomi, Emiliana; Caciagli, Patrizio; Midena, Edoardo; Nollo, Giandomenico
Abstract : Proliferative membranes of fibrocontractive retinal disorders are extensively studied from the morphological and evolutive point of view. Despite this, little is known of their cellular composition. In this study, the authors investigated the morphological characteristics and cell composition of various types of surgically excised proliferative membranes and internal limiting membranes (ILMs), in order to provide new data supporting or challenging the pathogenic theories proposed until now. Sixty-nine specimens from 64 eyes of 64 consecutive patients were collected at surgery and subjected to a multilevel analysis by means of optical and electron microscopy. Membrane samples were semiquantitatively evaluated for the amount and distribution of cell nuclei and pigment. Immunohistochemical staining was performed with antibodies to alpha smooth muscle actin and CD68. Data were analyzed after grouping according to the following tissue types: ILM (20 specimens), epiretinal membrane (ERM) (22 specimens), ILM + ERM (20 specimens), and proliferative vitreoretinopathy (PVR) (7 specimens). The cell components found in the ERM specimens, like myofibroblasts, macrophages, and polymorphonuclear cells, were recognized as the expression of cell migration and differentiation that induced an inflammatory process and a fibroproliferative repair process. The detection of pigments in specific types of ERM, like those associated with lamellar macular hole (LMH) or secondary to retinal detachment (RD), diabetes, and PVR, suggested that retinal pigment epithelium (RPE) cells may have a role in the development of these vitreoretinal disorders. The reduction of the ERM cellularity with the patient's age supports the hypothesis that ERM evolves in time up to a fibrous tissue formation.